2010
DOI: 10.1590/s1984-46702010000500010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the river flow on the structure of fish assemblage along the longitudinal gradient from river to reservoir

Abstract: ABSTRACT. Changes in fish assemblage structure along a longitudinal gradient of the Paraíba do Sul River and Funil reservoir were studied to detect distribution patterns and the seasonal influence of the inflowing river. Fish were caught by gill nets in three zones (riverine, transition and lentic) during two seasons (dry and wet). A total of 3,721 individuals were captured, comprising five orders, 14 families, 27 genera and 33 species. Five species were non-native and amounted to 17.7% of the total number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
11
0
4
Order By: Relevance
“…Attesting to the importance of the transition zone as a persistent speciose ecotone, Santos et al . () found greater species richness and diversity in the transition zone of a Brazilian Neotropical reservoir across both wet and dry seasons relative to that in riverine and lacustrine zones. Typically, the lacustrine and transition zones contribute most to the changes in fish assemblage composition and structure seen in impounded rivers (Oliveira et al , ; Santos et al ., ), and their effect becomes more pronounced in reservoirs further upstream as lacustrine zones comprise a progressively larger fraction of an impounded reach.…”
Section: Discussionmentioning
confidence: 99%
“…Attesting to the importance of the transition zone as a persistent speciose ecotone, Santos et al . () found greater species richness and diversity in the transition zone of a Brazilian Neotropical reservoir across both wet and dry seasons relative to that in riverine and lacustrine zones. Typically, the lacustrine and transition zones contribute most to the changes in fish assemblage composition and structure seen in impounded rivers (Oliveira et al , ; Santos et al ., ), and their effect becomes more pronounced in reservoirs further upstream as lacustrine zones comprise a progressively larger fraction of an impounded reach.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RRI fish assemblages should be included in integrated management efforts aimed at conserving native riverine fish assemblages and maintaining sport fisheries in river–reservoir ecosystems. Similar research of transitional habitats between rivers and reservoirs in Brazil has also reported highly diverse fish assemblages representing both riverine and lentic species (Carvalho et al ., ; Oliveira et al ., ; Santos et al ., ; Terra et al ., ), suggesting that these findings may be applicable to other regulated rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Although artificial, RRIs incorporate many features of adjacent river and reservoir habitats and may function similar to ecotones of natural systems, which support highly diverse assemblages (Odum, ). Recent studies generally support this idea, finding high fish species richness in transitional habitats between reservoirs and their upstream tributaries (Carvalho et al ., ; Oliveira et al ., ; Kaemingk et al ., ; Santos et al ., ; Terra et al ., ; Yang et al ., ). Transitional habitats associated with RRIs can also support high zooplankton species richness (Nogueria et al ., 2008) and be important for phytoplankton production (Scott et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the high abundance of piscivores, the most frequently captured species in this reservoir (Geophagus proximus) was usually found in the lacustrine zone. Santos et al (2010) found that a Geophagus species was also among the most abundant species in Funil Reservoir, southeastern Brazil. It exhibited restricted distribution to lacustrine sites, to which Geophagus species are well adapted.…”
Section: Effect Of Reservoir Zone On Fish Assemblage Abundance and Richmentioning
confidence: 92%